The Use of Genotoxicity Endpoints as Biomarkers of Low Dose Radiation Exposure in Interventional Cardiology - Habibi, Martha; Karyofyllis, Panagiotis K.; Nikolakopoulou, Aggeliki; Papagiannis, Panagiotis; Karaiskos, Pantelis; Georgakilas, Alexandros G.; Hatzi, Vasiliki I.; Malakos, Ioannis; Kollaros, Nikolaos; Mastorakou, Irene; Voudris, Vassilis; Terzoudi, Georgia I. (Frontiers in Public Health, 2021)
The effect of the reportedly low ionizing radiation doses, such as those very often delivered to patients in interventional cardiology, remains ambiguous. As interventional cardiac procedures may have a significant impact on total collective effective dose, there are radiation protection concerns for patients and physicians regarding potential late health effects. Given that very low doses (<100 mSv) are expected to be delivered during these procedures, the purpose of this study was to assess the potency and suitability of current genotoxicity biomarkers to detect and quantitate biological effects essential for risk estimation in interventional cardiology. Specifically, the biomarkers γ-H2AX foci, dicentric chromosomes and micronuclei, which underpin radiation-induced DNA damage, were studied in blood lymphocytes of 25 adult patients before and after interventional cardiac procedures. Even though the mean values of all patients as a group for all three endpoints tested show increased yields relative to baseline following medical exposure, our results demonstrate that only the γ-H2AX biomarker enables detection of statistically significant differences at the individual level (p<0.001) for almost all patients (91%). Furthermore, 24 hours after exposure, residual γ-H2AX foci were still detectable in irradiated lymphocytes. Their decline was found to vary significantly among the individuals and the repair kinetics of γ-H2AX foci was found to range from 25% to 95.6% of their maximum values obtained.